2011
DOI: 10.1007/s10803-011-1339-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Social Skills Training for Adolescents with Autism Spectrum Disorders: The UCLA PEERS Program

Abstract: The present study examines the efficacy and durability of the PEERS Program, a parent-assisted social skills group intervention for high-functioning adolescents with ASD. Results indicate that teens receiving PEERS significantly improved their social skills knowledge, social responsiveness, and overall social skills in the areas of social communication, social cognition, social awareness, social motivation, assertion, cooperation, and responsibility, while decreasing autistic mannerisms and increasing the freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
334
4
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(367 citation statements)
references
References 46 publications
25
334
4
4
Order By: Relevance
“…Overall, results from this study suggest that the PEERS intervention offers promising adjunctive benefits for families in addition to the improved teen social outcomes resulting from PEERS demonstrated in the larger project encompassing this study as well as those conducted by others research groups (e.g., Laugeson et al 2011;Mandelberg et al 2014;Schohl et al 2014). The significant time × group interaction found on the CHAOS highlights the way in which the PEERS intervention, through the use of concurrent parent and teen sessions, may help improve the trajectory of family chaos or dysfunction for families heavily burdened by their child's diagnosis and associated impairments.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Overall, results from this study suggest that the PEERS intervention offers promising adjunctive benefits for families in addition to the improved teen social outcomes resulting from PEERS demonstrated in the larger project encompassing this study as well as those conducted by others research groups (e.g., Laugeson et al 2011;Mandelberg et al 2014;Schohl et al 2014). The significant time × group interaction found on the CHAOS highlights the way in which the PEERS intervention, through the use of concurrent parent and teen sessions, may help improve the trajectory of family chaos or dysfunction for families heavily burdened by their child's diagnosis and associated impairments.…”
Section: Discussionmentioning
confidence: 51%
“…The PEERS program uses a variety of cognitive-behavioral principles to help enhance the social functioning of adolescents with ASD (see Table 1). Preliminary research on PEERS has identified significant social skills and friendship improvements in adolescents with ASD immediately following intervention and at 14-week follow-up (Laugeson et al 2011), as well as up to 5 years post-treatment (Mandelberg et al 2014). Mandelberg et al noted in their long-term outcome study that parent involvement in this intervention likely plays a large role in the maintenance of treatment gains from PEERS.…”
Section: Social Skills Interventions For Asdmentioning
confidence: 99%
“…This is despite the fact that ABA procedures have empirically demonstrated improvements for specific and overall social behaviors for high-functioning individuals diagnosed with ASD (Brodhead et al 2014;Kamps et al 1992;Koegel et al 1992;Koegel and Frea 1993;Laugeson et al 2012;Leaf et al 2015;Nikopoulous 2007;Weiss and Harris 2001).…”
Section: Does Social Thinking® Make Negative Statements About Other Pmentioning
confidence: 99%
“…more dominant left hemisphere asymmetry). A negative correlation between gamma asymmetry and scores on the Quality of Socialization Questionnaire-Revised (QSQ-R; Laugeson et al, 2012), a questionnaire completed by parents, which rates the frequency of peer interactions and get-togethers, was observed. Finally, a positive correlation between left-dominant asymmetry and the Social Responsiveness Scale total score (SRS; Constantino, 2005), a parent-report measure of global autism symptomology, was observed.…”
Section: Authorsmentioning
confidence: 99%
“…Further, these results provide evidence that participation in PEERS increases this asymmetry such that differences observed at baseline between the PEERS group and TD children are no longer observed at post-test. Correlations between gamma asymmetry values and behavioral measures of interest revealed that higher scores on the Test of Adolescent Social Skills Knowledge (TASSK; Laugeson et al, 2012), a questionnaire designed to measure knowledge of the PEERS curriculum upon post-test, were related to lower gamma asymmetry (e.g. more dominant left hemisphere asymmetry).…”
Section: Authorsmentioning
confidence: 99%